2005
DOI: 10.1051/0004-6361:20042365
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric NLTE-models for the spectroscopic analysis of blue stars with winds

Abstract: Abstract. We present new or improved methods for calculating NLTE, line-blanketed model atmospheres for hot stars with winds (spectral types A to O), with particular emphasis on fast performance. These methods have been implemented into a previous, more simple version of the model atmosphere code F (Santolaya-Rey et al. 1997) and allow us to spectroscopically analyze large samples of massive stars in a reasonable time-scale, using state-of-the-art physics. Although this updated version of the code has a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
534
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 447 publications
(550 citation statements)
references
References 46 publications
14
534
0
2
Order By: Relevance
“…We derived the stellar atmospheric parameters using a grid of synthetic stellar atmosphere models built using the atmosphere/line formation code fastwind (Santolaya-Rey et al 1997;Puls et al 2005;Rivero González et al 2012). The code takes into account non-local thermo-dynamical equilibrium effects in spherical symmetry with an explicit treatment of the stellar wind.…”
Section: Observations Data Reduction and Resultsmentioning
confidence: 99%
“…We derived the stellar atmospheric parameters using a grid of synthetic stellar atmosphere models built using the atmosphere/line formation code fastwind (Santolaya-Rey et al 1997;Puls et al 2005;Rivero González et al 2012). The code takes into account non-local thermo-dynamical equilibrium effects in spherical symmetry with an explicit treatment of the stellar wind.…”
Section: Observations Data Reduction and Resultsmentioning
confidence: 99%
“…Additionally, a normal helium to hydrogen ratio of 0.1 by number of atoms was assumed. The validity of such an approach was investigated by Dufton et al (2005), who analysed the spectra of B-type Ia supergiants in the SMC using the current grid and also theoretical spectra generated by the  code (Santolaya-Rey et al 1997;Puls et al 2005), that incorporates wind effects. Dufton et al (2005) found excellent agreement in the atmospheric parameters estimated from the two methods.…”
Section: Methodsmentioning
confidence: 99%
“…While detailed information about the latest version used here can be found in Puls et al (2005), we highlight only those points which are important for our analysis of B stars.…”
Section: Determination Of Stellar and Wind Parametersmentioning
confidence: 99%